Characterization of Guar Cultivar, Extraction of Guar Gum and Their Application in Bakery Products as a Fat Replacer: Guar Gum Added Cookies and Cakes (Biological Sciences - PJSIR, 2026)
The examination had been carried out to find out how guar gum affects the nutritional and qualitative characteristics of bakery goods, particularly cookies and cakes. At first guar beans were analyzed for their different physiochemical characteristics and guar gum was produced from guar beans. Then, using various concentrations, guar gum was introduced as a fat substitute in cookies and cakes. After thorough examination of these items, assessing a variety of quality factors, nutritional characteristics and sensory qualities. The prepared products will be assessed in terms of quality factors, nutritional characteristics and sensory attributes. According to the research, the mean values of the components of cookies’ moisture, fat, ash, protein and fibre ranged from 2.98% to 3.35%, 9.36% to 15.05%, 1.41% to 2.17%, 6.64% to 7.34% and 1.41% to 2.17%, respectively. Similar results were found for cakes, where the mean values for moisture, fat, ash, protein and fibre, respectively, ranged from 19.06% to 23.03%, 6.70% to 7.34%, 12.6%to 15.17%, 1.55% to 2.35% and 1.49% to 2.22%. Physical factors including cookie thickness, spread factor and hardness as well as sensory traits were significantly altered. Additionally, the presence of guar gum had a significant impact on the physiochemical characteristics (volume and colour) and sensory qualities of cakes. The results of this physiochemical and sensory analysis conclusively showed that guar gum addition significantly increase the positive impact on the quality characteristics and customer acceptance of a variety of bakery items.